The Influence of Principal Leadership and Infrastructure Facilities on Teacher Performance Mediated by Teacher Satisfaction (Case Study at Smpk 3 Penabur) - Mirra Kurnianingsih; Soegeng Wahyoedi; Jimmy Lizardo (PT. Anagata Sembagi Education, 2024)
Education is the main foundation in shaping the next generation of quality. In this context, teacher performance plays a central role in achieving the goal of quality education. However, teacher performance is not only influenced by individual factors, but also by external factors such as school leadership and the availability of infrastructure. Effective leadership and adequate infrastructure can positively influence teacher performance. Leadership that is visionary and able to provide clear direction can motivate and inspire teachers to give their best in learning. In the context of formal education, the principal leadership is an important element that determines the direction and success of the school. This research will delve deeper into the importance of human resources in schools, especially the principal leadership as a leader. Quality schools are not only determined by physical facilities and curriculum, but also the quality of teachers, staff and effective leadership.Principal leadership as an agent of change has a strategic role in managing school human resources. Visionary and inclusive leadership can form a positive work culture, increase teacher motivation and performance, and design development policies according to educational developments. This study aims to determine the effect of principal leadership and infrastructure facilities on teacher performance mediated by teacher satisfaction. Located in (Case Study at SMPK 3 PENABUR and totaling 30 (Thirty) people and all members of the population as well as samples so that this research is census research. The results of this analysis show that all indicators used in this study are valid and reliable. This study uses a Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS) using SmartPLS 3.3 software. This study provides evidence of a positive and significant effect